Evaluation of the Properties of Cellulose Ester Films that Incorporate Essential Oils - Atanu Biswas; Maria do Socorro Rocha Bastos; Roselayne Ferro Furtado; Gary Kuzniar; Veera Boddu; H. N. Cheng (International Journal of Polymer Science)
Films made from cellulose esters are often used as bio-based food packaging materials. In this work, we studied the incorporation of nine essential oils into cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate. The essential oils were derived from lime, nutmeg, eugenol, pimenta berry, rosemary, petitgrain, coffee, anise, and trans-cinnamaldehyde. In almost all cases, the addition of essential oils to cellulose ester reduced tensile strength and Young’s modulus but increased elongation at break. Thus, an essential oil acted like a plasticizer that enhanced the flexibility of the polymer. Essential oils containing limonene and pinenes (e.g., from lime and nutmeg) gave the strongest plasticizing action, whereas essentials oils containing fatty acids (e.g., from coffee) were the weakest plasticizers. The water barrier property was improved the most when essential oils were added to cellulose acetate; however, different cellulose ester/essential oil combinations showed different effects. Whereas most of the essential oils decreased the transparency of the films, eugenol, pimento berry, and anise were notable exceptions. Thus, depending on a specific application, a particular polymer/EO combination can be used to give the optimal performance.